The Abstention Phenomenon in the 2024 Mandailing Natal Regional Election in Qur'anic Perspective - Gustianda, Nana; Adhli, Aulya; Amiruddin, Amiruddin; Aini, Syaripah; Afriza, Nugraha Andri (Jurnal Kajian dan Pengembangan Umat, 2025)
The phenomenon of non-voting (golput) or voter abstention in elections presents a significant challenge to democracy in Indonesia, including in the 2024 Mandailing Natal Regional Election. Low political participation can undermine the legitimacy of elected governments and hinder regional development processes. In the context of Islam, political participation can be viewed as part of the social responsibility taught in the Qur'an, which emphasizes the importance of deliberation, justice, and trustworthiness in societal life. This study employs a qualitative-descriptive approach with data collected through in-depth interviews with non-participating voters in the 2024 Mandailing Natal Regional Election and secondary data analysis from reports by the General Election Commission (KPU) and relevant literature. The Qur'anic perspective is examined using the thematic interpretation (maudhu’i) method, tracing verses related to political participation. The study finds that the main factors driving non-voting in Mandailing Natal include: (1) public distrust in candidates perceived as incapable of bringing change, (2) political apathy due to money politics, and (3) limited understanding of the importance of political participation in Islam. From the Qur'anic perspective, abstention can be considered contrary to the principle of shura (deliberation), as stated in QS. Ash-Shura (42:38), and the obligation to uphold justice in QS. An-Nisa (4:58).